Cortical control of striatal dopamine transmission via striatal cholinergic interneurons - Kosillo, P; Zhang, Y; Threlfell, S; Cragg, S (Oxford University Press, 2016)
Corticostriatal regulation of striatal dopamine (DA) transmission has long been postulated, but ionotropic glutamate receptors have not been localized directly to DA axons. Striatal cholinergic interneurons (ChIs) are emerging as major players in striatal function, and can govern DA transmission by activating nicotinic receptors (nAChRs) on DA axons. Cortical inputs to ChIs have historically been perceived as sparse, but recent evidence indicates that they strongly activate ChIs. We explored whether activation of M1/M2 corticostriatal inputs can consequently gate DA transmission, via ChIs. We reveal that optogenetic activation of channelrhodopsin-expressing corticostriatal axons can drive striatal DA release detected with fast-scan cyclic voltammetry and requires activation of nAChRs on DA axons and AMPA receptors on ChIs that promote short-latency action potentials. By contrast, DA release driven by optogenetic activation of intralaminar thalamostriatal inputs involves additional activation of NMDA receptors on ChIs and action potential generation over longer timescales. Therefore, cortical and thalamic glutamate inputs can modulate DA transmission by regulating ChIs as gatekeepers, through ionotropic glutamate receptors. The different use of AMPA and NMDA receptors by cortical versus thalamic inputs might lead to distinct input integration strategies by ChIs and distinct modulation of the function of DA and striatum.